Thyroid and androgen receptor signaling are antagonized by μ‐Crystallin in prostate cancer. Issue 3 (31st October 2020) - Aksoy, Osman; Pencik, Jan; Hartenbach, Markus; Moazzami, Ali A.; Schlederer, Michaela; Balber, Theresa; Varady, Adam; Philippe, Cecile; Baltzer, Pascal A.; Mazumder, Bismoy; Whitchurch, Jonathan B.; Roberts, Christopher J.; et al.
Abstract: Androgen deprivation therapy (ADT) remains a key approach in the treatment of prostate cancer (PCa). However, PCa inevitably relapses and becomes ADT resistant. Besides androgens, there is evidence that thyroid hormone thyroxine (T4) and its active form 3, 5, 3′‐triiodo‐L ‐thyronine (T3) are involved in the progression of PCa. Epidemiologic evidences show a higher incidence of PCa in men with elevated thyroid hormone levels. The thyroid hormone binding protein μ‐Crystallin (CRYM) mediates intracellular thyroid hormone action by sequestering T3 and blocks its binding to cognate receptors (TRα/TRβ) in target tissues. We show in our study that low CRYM expression levels in PCa patients are associated with early biochemical recurrence and poor prognosis. Moreover, we found a disease stage‐specific expression of CRYM in PCa. CRYM counteracted thyroid and androgen signaling and blocked intracellular choline uptake. CRYM inversely correlated with [18F]fluoromethylcholine (FMC) levels in positron emission tomography/magnetic resonance imaging of PCa patients. Our data suggest CRYM as a novel antagonist of T3‐ and androgen‐mediated signaling in PCa. The role of CRYM could therefore be an essential control mechanism for the prevention of aggressive PCa growth. Abstract : What's new? Thyroid hormones may play a role in the progression of prostate cancer (PCa). In this study, the authors found that PCa cells had decreased expression of the thyroid‐hormone‐binding protein μ‐Crystallin (CRYM). Lower CRYM was also associated with poor prognosis in men with PCa. In addition, CRYM inhibited thyroid‐hormone and androgen signaling, as well as 18F‐fluoromethylcholine uptake by PCa cells. These results suggest that CRYM may act as a novel antagonist against factors that fuel PCa progression, and therefore thyroid signalling may offer a new therapeutic target in slowing aggressive prostate cancer.